The Prehistoric Economics of the Kautz Site: a Late Archaic and Woodland Site in Northeastern Illinois - (:unkn) unknown (My University, 2016)
The Kautz Site (11DU1) is a multi-component archaeological site located in the DuPage River Valley in northeastern Illinois. It was inhabited at least six different times between the Late Archaic and Late Woodland periods ca. 6000-1000 B.P. The site was excavated over the course of three field seasons between 1958 and 1961, but the results were never made public. This thesis seeks to document the archaeology of the Kautz Site in order to better understand the site’s economic history. An environmental catchment analysis was conducted to evaluate the level of time and energy needed to acquire important resources like water, food, wood, and chert. A macroscopic analysis of the lithic assemblage provided information about the lithic economy at the site. The results of the landscape analysis suggest that the site was located in an economically efficient location, however the macroscopic analysis suggests that a source of raw materials for chipped stone tools was not easily accessible and as a result the inhabitants practiced a number of common adaptive strategies to cope with resource scarcity.
Keywords: Archaeology; Chicago; GIS; Illinois; Landscape; Lithics